How a Social Network Profile Affects Employers' Impressions of the Candidate: An Application of Norm Evaluation. (August 2020) - Rui, Jian Raymond
Employers have used social network sites (SNSs) to screen job candidates. However, the mechanism by which SNS posts shape employers' impressions of the candidates is unclear in previous research. Two studies were conducted to examine how employers develop impressions of job candidates by evaluating their SNS profile against perceived organizational and societal injunctive norms (perceived organizational injunctive norms [POINs] and perceived societal injunctive norms [PSINs], respectively), through a 2 (SNS profile type: alcohol-free vs. alcohol-included) × 2 (industry: Catholic school vs. information technology [IT]) × 2 (gender-role perceptions based on candidate's sex: male vs. female) between-subjects experiment design. Findings contribute to the scholarship on impression formation via SNSs by showing that individuals develop their impressions by evaluating how much the target SNS profile aligns with POINs. Specifically, an alcohol-included Facebook profile violated POINs and PSINs more than an alcohol-free profile. In addition, both studies found that the interaction effect between the profile and the industry on the extent to which the SNS profile aligned with POINs and PSINs was significantly different for the male and female candidate. This research offers practical implications about how to manage professional self-presentation on SNSs.